(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study’s goal was to find out the admission surface amount (ESD), maximum effective dose (ED), organ administer the dose, and regional dose rates throughout three general medical centers using a common screening via radiography tests. Over the course of six months, radiological machines and four via radiography views were used to gather data from 110 patients. Studies showed that changes in mAs and kVp were strongly linked to changes in ED and ESD morals. The overall mean ESD was smaller than the suggested DRLs, but the ED estimated was higher than that of the other research. We use findings from the research to find the best dose levels for patients.